Research Progress on the Application of Nanoenzyme Electrochemical Sensors for Detecting Zearalenone in Food - Guoqiang Guan; Zhiyuan Lin; Jingya Qian; Feng Wang; Liang Qu; Bin Zou (Nanomaterials)
Zearalenone (ZEN) is a common mycotoxin widely found in food crops such as corn. The toxicity of ZEN is manifested as multiple hazards to reproduction, genes, cells, and immune systems. Long-term exposure may have a serious impact on health, so it has received extensive attention due to its potential harm to human and animal health. In order to ensure food safety, countries have formulated corresponding ZEN content limit standards and promoted the development of efficient and rapid detection technologies. This paper reviews the research progress of ZEN detection in food based on nanoenzyme electrochemical sensors. Firstly, the basic situation of ZEN was introduced, including its physical and chemical properties, toxicity, and related regulations and standards. Secondly, the advantages and disadvantages of traditional detection methods and new detection technologies are analyzed, and the application progress of electrochemical sensors in ZEN detection is discussed, especially aptamer electrochemical sensors, immune-electrochemical sensors, and nanoenzyme electrochemical sensors. In this paper, the advantages of nanoenzyme electrochemical sensors in ZEN detection are discussed in detail, especially in terms of sensitivity, selectivity, and rapid detection. However, nanoenzyme electrochemical sensors still face some challenges in practical applications, such as high production costs, control of signal amplification effects, and safety issues of nanomaterials. Finally, this paper looks forward to the future development direction of nanoenzyme electrochemical sensors and proposes possible solutions to further improve their stability, reduce costs, and optimize sensing performance.